Preschoolers’ decisions in resource distribution : the effects of agents’ prosocial- antisocial behavior and group membership - Wang, Valerie Yunxi (2016)
Research looking at children’s sociomoral reasoning has commonly examined the principles of fairness, ingroup loyalty, and no-harm independently in Western cultures. However, less is known about how these principles can operate together to influence children’s behavior. Using a third-party resource distribution paradigm, the present study aimed to investigate how children’s distribution decisions and choice preferences would be influenced in contexts where a conflict between the principles of no-harm and ingroup loyalty arises. Three experiments were conducted on preschoolers in Singapore and it was predicted that an agent’s social behavior (antisocial or prosocial) and group membership would influence their decisions on resource distribution and their preferred agent. In Experiment 1 (n = 48), when no groups were assigned, results showed that 26- to 40-month-olds distributed more resources to a prosocial agent but did not express preference for the prosocial or antisocial agent. In Experiment 2 (n = 64), 30- to 43-month-olds distributed more resources to the prosocial agent when the ingroup agent was antisocial. However, 44- to 60-month-olds did not display any specific distribution patterns. In Experiment 3 (n = 32), 40- to 72-month-old boys, but not girls, distributed more resources to an ingroup member in both ingroup prosocial and ingroup antisocial conditions. Lastly, both Experiments 2 and 3 found that preschoolers favorably choose an ingroup agent, regardless of their social behavior. These findings suggest that preschoolers in Singapore are able to demonstrate moral considerations in contexts where sociomoral principles interact, and have implications in individuals’ moral expectations and decisions.